Frequency of gene hMLH1 promoter methylation in the stomach antral and body area tissue of chronic atrophic pangastritis patients - Kupčinskaitė-Noreikienė, Rita; Jančiauskas, Dainius; Juozaitytė, Elona (Acta medica Lituanica, 2013)
Aim. To compare hMLH1 methylation frequency in stomach antral and body area tissue in chronic atrophic pangastritis patients, and to evaluate possible correlation severity of chronic atrophic gastritis markers. Methods. The study population consisted of 24 participants (with histologically confirmed chronic atrophic pangastritis), who underwent upper endoscopy. Biopsy specimens were taken from the gastric antral and body area. The methylation status of the gene hMlH1 was investigated. Results. Methylation of the CpG island of gene hMLH1 was found in the antral stomach area group 9/24, compared with the body area 2/24. There was a significant difference in gene methylation frequencies in the observed stomach parts (Fisher’s exact test, p = 0.04). There was a significant association between gene hMLH1 methylation and the occurrence of severe atrophic gastritis, intestinal metaplasia and the presence of hyperplastic mucosal changes (Fisher’s exact test, p